2014
DOI: 10.1038/nature13185
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional landscape of the prenatal human brain

Abstract: SummaryThe anatomical and functional architecture of the human brain is largely determined by prenatal transcriptional processes. We describe an anatomically comprehensive atlas of mid-gestational human brain, including de novo reference atlases, in situ hybridization, ultra-high resolution magnetic resonance imaging (MRI) and microarray analysis on highly discrete laser microdissected brain regions. In developing cerebral cortex, transcriptional differences are found between different proliferative and postmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
1,211
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,180 publications
(1,320 citation statements)
references
References 62 publications
44
1,211
1
1
Order By: Relevance
“…However, more recent studies in ferret (Reillo and Borrell, 2012) and macaque (Betizeau et al, 2013) have shown that the cellular composition of ISVZ and OSVZ is very similar and both contain oRG and IPCs than was previously appreciated. This is also in agreement with the finding that gene expression profiles of ISVZ and OSVZ in the human developing neocortex are closely related to each other (Fietz et al, 2012; Miller et al, 2014). …”
Section: Does the Isocortex Of All Eutherian Mammals Develop From A Gsupporting
confidence: 91%
“…However, more recent studies in ferret (Reillo and Borrell, 2012) and macaque (Betizeau et al, 2013) have shown that the cellular composition of ISVZ and OSVZ is very similar and both contain oRG and IPCs than was previously appreciated. This is also in agreement with the finding that gene expression profiles of ISVZ and OSVZ in the human developing neocortex are closely related to each other (Fietz et al, 2012; Miller et al, 2014). …”
Section: Does the Isocortex Of All Eutherian Mammals Develop From A Gsupporting
confidence: 91%
“…We narrowed down the candidate-gene list by excluding NHSL2 (Gene ID: 340527), AMER1 (Gene ID: 139285), PHKA1 (Gene ID: 5255) and RGAG1 (Gene ID: 57529) based on evolutionary analysis, gene expression profiles in tissues and protein topology position (Supplementary Figure 1). NHSL2 gene was excluded because there are no reports on association of rare variants in the NHSL2 gene, including the rs72630038 (SCV000221324) (MAF = 0.045 in 1000 Genomes Project Consortium 15 ) found in the Buryat patient, with any disorder; low expression of the gene in the cerebellum at prenatal period; 16,17 and that at least one mammalian species (hedgehog) bears the same rare amino-acid variant in NHSL2. Mutations in the AMER1 gene are known as genetic factors underlying osteopathia striata, cranial sclerosis and intellectual disability syndrome (OMIM: 300647 and 300373).…”
Section: Whole-genome Sequencingmentioning
confidence: 99%
“…Given the many ways in which complex diseases arise, and for human brain diseases, the well‐recognized cellular heterogeneity of the brain, pinpointing cell types of interest, is important to further understand pathogenicity. Efforts to obtain brain samples (the most obviously relevant tissue for neurodegenerative diseases) for eQTL analyses are ongoing 8, 9, 10, 11, 12, 13. There has been a recent proliferation in the availability of cell‐type and tissue‐specific annotations, including brain tissue, for example, through the Roadmap Epigenomics Project14 and the PsychEncode Project 11.…”
Section: Introductionmentioning
confidence: 99%